Delimitation of the Rural Population Sets of the Region of Altiplano in the Region of Murcia - Sánchez-Sánchez, Miguel Ángel (Revista de Estudios Andaluces, 2019)
The objective of this work has been to determine that human settlements in the Jumilla-Yecla Altiplano region of the Murcia Region can be classified as rural population groups. This question is of interest within the scope of the Territorial Ordinance Guidelines of the region. To do this, flow diagrams were devised, with conditions such as: being a population nucleus and being located in rural areas, which had to comply with the human settlements studied –exception of the archaeological sites–. Only nine elements were qualified as villages, among the forty-nine cases studied. This work has allowed a first approximation to the definition-determination of rural population in the study area.